Late stroke after transcatheter aortic valve replacement: a nationwide study - Henrik Bjursten (Nature Portfolio, 2021)
Abstract Transcatheter aortic valve replacement (TAVR) is a rapidly growing field. Short-term safety and efficacy of these procedures have been studied extensively. However, little is known about the safety of these devices over time. Stroke is one feared long-term complication, and an increased stroke rate could affect guidelines for treating both the aortic stenosis and choosing antithrombotic therapy after TAVR. The primary objective was to study the incidence of stroke up to 8 years after TAVR implantation, comparing it with the risk of stroke in the general population. Secondary objectives were to study risk factors for late stroke and to study outcomes after stroke. A nationwide, all-comers study of patients who underwent TAVR in Sweden 2008–2018 was performed. The study was based on data from three national registries: a TAVR registry, a stroke registry, and a diagnosis registry. The main outcome was stroke incidence 30-days or more after TAVR implantation and was compared to a standardized incidence. The annual risk for stroke varied between 2.0% and 3.1% as compared to 1.5% and 1.9% in an age- and sex-matched cohort. Risk factors for developing stroke were reduced renal function, diabetes, history of stroke, age, and male sex. The 1-year mortality after stroke was 44%. This study demonstrated an increased rate of stroke after TAVR, but the findings suggest that this can in part be attributed to the group’s higher frequency of pre-disposing risk factors.